Analisis Proses Politik Uji Mampu Baca Al-Qur’an Calon Anggota DPRA Dan DPRK Bagi Partai Politik Nasional Di Provinsi Aceh - Nana Nana; R. Hamdani Harahap; Heri Kusmanto (PERSPEKTIF, 2021)
This study aims to identify and analyze the political process for the implementation of the Al-Qur'an Reading Ability Test for National Political Parties participating in the 2019 General Election in Aceh Province. Based on the problem, the author chose to use qualitative research in this study, where the author can explain how the political process towards the implementation of the Qur'anic reading test and the reasons for the national party in accepting and taking the test of being able to read the Qur'an for legislative candidates in the 2019 election. General Simultaneous 2019, which incidentally did not regulate the implementation of the Qur'an reading test for prospective legislative candidates from national parties, but in Aceh requires this rule. The results of this study are not far from the author's initial assumptions where the results of the study show that the political process of being able to read the Qur'an for national political parties is not only to maintain Islamic law as an important part of the specificity of Aceh contained in the UUPA, but also as an effort to fulfill the party's interests. politics so that their existence and electability will continue to increase in every stage of the legislative general election in Aceh. And this is relevant to the theory of political actors mentioned by Mosca that actors are the holders of strategic positions or positions in the executive, namely in KIP Aceh and have the influence to add policies in the legislative elections in Aceh for the sake of Aceh as an Islamic Shari'a area.